MODEL OFF-LINE UNTUK SIMULASI PROSES PEMURNIAN BAJA DI VACUUM TANK DEGASSER (VTD) [Off-Line Model for Refining Steel Process Simulation in Vacuum Tank Degasser (VTD) - Zulhan, Zulfiadi (Jurnal Metalurgi, 2012)
OFF-LINE MODEL FOR REFINING STEEL PROCESS SIMULATION IN VACUUM TANK DEGASSER (VTD). Vacuum Tank Degasser (VTD) has been applied in industry to produce high quality steel especially for steel products which have low hydrogen and nitrogen contents as well as ultra low carbon and sulphur contents. An off-line model was developed and presented in this paper to simulate process steps to be performed on VTD starting from ladle arriving treatment position, vacuum treatment, flooding till treatment end. Furthermore, this off-line model could be used as Level 2 automation control system for operator guider. Steel temperature, carbon, nitrogen, hydrogen and sulphur contents and the possibility for steel boiling during vacuum treatment can be predicted using this model.